PLÁCIDO, D.; MANZANO, E.; SALRACH, J. M.; ALLMAND, GIL NOVALES, A.; RIQUER,B. de; UCELAY DA CAL, E.; MOLINERO, C.; y ISÁS. P.: lles. Jornades de debat . El poder de l´Etat: Evolució, força o raó. - Rojas Friend, Antonio (Historia y Comunicación Social, 1996)
Sin resumen